Rational Improvement of Molar Absorptivity Guided by Oscillator Strength: A Case Study with Furoindolizine‐Based Core Skeleton. (13th November 2015) - Lee, Youngjun; Jo, Ala; Park, Seung Bum
Abstract: The rational improvement of photophysical properties can be highly valuable for the discovery of novel organic fluorophores. Using our new design strategy guided by the oscillator strength, we developed a series of full‐color‐tunable furoindolizine analogs with improved molar absorptivity through the fusion of a furan ring into the indolizine‐based Seoul fluorophore. The excellent correlation between the computable values (oscillator strength and theoretical S0 –S1 energy gap) and photophysical properties (molar absorptivity and emission wavelength) confirmed the effectualness of our design strategy. Abstract : Eine rationale Designstrategie basierend auf der Oszillatorstärke ermöglichte den Zugang zu einem Furo[3, 2‐ e ]indolizin‐basierten fluoreszierenden Kerngerüst mit verbessertem molarem Absorptionsgrad. Ein Furanring wurde in einen Indolizin‐basierten Seoul‐Fluorophor fusioniert, um die Vorhersagbarkeit der photophysikalischen Eigenschaften zu demonstrieren.